2020
DOI: 10.21203/rs.3.rs-48454/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neural Processing of Speech Sounds in ASD and First-Degree Relatives

Abstract: Background: Efficient neural encoding of sound plays a critical and widespread role in speech and language, and when impaired, may have reverberating effects on a range of communication skills. Autism spectrum disorder (ASD) is a condition involving impaired communication abilities, including atypical prosody (e.g., intonation modulation, rate, rhythm), in which atypical neural processing of speech has been implicated. Parallel patterns of communication differences have been noted in parents of individuals wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 29 publications
(38 reference statements)
1
4
0
Order By: Relevance
“…Furthermore, the present study identified key associations that suggest differential parentchild relationships for mothers and fathers, where only mothers' BAP characteristics and childhood language abilities were related to siblings' language abilities. Indeed, a growing body of literature has suggested that the presence and quality of ASD endophenotypes differ among mothers and fathers, as do relationships between parent endophenotypes and their child's clinical behavioral presentation (33,43,83,(92)(93)(94). Consistent with the results reported here, several studies have found BAP traits in mothers, but not fathers, to be linked to child language abilities in individuals with ASD (34,83,92,93).…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Furthermore, the present study identified key associations that suggest differential parentchild relationships for mothers and fathers, where only mothers' BAP characteristics and childhood language abilities were related to siblings' language abilities. Indeed, a growing body of literature has suggested that the presence and quality of ASD endophenotypes differ among mothers and fathers, as do relationships between parent endophenotypes and their child's clinical behavioral presentation (33,43,83,(92)(93)(94). Consistent with the results reported here, several studies have found BAP traits in mothers, but not fathers, to be linked to child language abilities in individuals with ASD (34,83,92,93).…”
Section: Discussionsupporting
confidence: 87%
“…Such weaknesses in linguistic fluency and speech sound processing may have downstream impacts on functional language abilities such as pragmatic language skills. Deeper explorations of pragmatic phenotypes have also revealed discrepancies from controls in the acoustic characteristics of speech that are similar to those observed in ASD and characterized by differences in intonation, modulation of volume, rate of speech, and stress patterns (30,(41)(42)(43). Pragmatic language difficulties have further been evidenced among parents through subtle differences in narrative generation, characterized by decreased complexity and coherence, with overall narrative quality subject to context variability (40).…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Over the years, my team has published a few studies on auditory processing in autism and I have written about the topic here in Hearing Matters. 1,2 In a new study published in the Journal of Autism and Developmental Disorders 3, my colleagues down the hall at the Northwestern University Neurodevelopmental Disabilities Lab, headed by Dr. Molly Losh, teamed up with my Brainvolts Lab to look at sound processing not only in people with autism, but in parents of people with autism.…”
mentioning
confidence: 99%